CORRELATION OF SERUM SCLEROSTIN LEVELS WITH CAROTID INTIMA MEDIA THICKNESS IN CHRONIC KIDNEY DISEASE HEMODIALYSIS - Permana, Adhi; Effendi, Ian; Indrajaya, Taufik (Biomedical Journal of Indonesia, 2020)
Chronic kidney disease is associated with a high mortality rate, especially cardiovascular disease associated with mineral and bone disorders. Sclerostin is an inhibitor of Wnt signaling which has the effect of increasing the occurrence of vascular calcification in patients with chronic kidney disease. There are several studies that show different results. Carotid intima media thickness ultrasound examination is a tool to identify atherosclerosis which is part of vascular calcification. The aim of this study is to look at the correlation of sclerostin with carotid intima media thickness (CIMT) in patients with chronic kidney disease undergoing hemodialysis. In this cross section, the concentration of sclerostin was measured by examination of enzymed linked immunosorbent assay. CIMT measurement by ultrasound mode B examination. There were 40 patients in this study. The mean sclerostin level was 256.68 ± 127.76 pg / ml. Sclerostin levels are declared high if above 162 pg / ml there are 30 people. CIMT thickening was present in 11 patients. There was no significant correlation of serum sclerostin with CIMT in patients with chronic kidney disease undergoing hemodialysis (r-0.32 p0,847). In multivariate linear regression, hemodialysis duration is an independent factor that is significantly significant with CIMT. There was no significant correlation of serum sclerostin with CIMT in patients with chronic kidney disease undergoing hemodialysis.